Clinical outcomes and transfusion management following intracranial hemorrhage in patients with acute leukemia. Issue 2 (6th December 2019) - Nixon, Shannon; Lieberman, Lani; Atenafu, Eshetu G.; Doherty, Mary; Murray, Cindy; Wolfe, Amanda; Brandys, Danielle; Rowland, Suzanne; Kwan, Benjamin YM; Yu, Eugene; Lechner, Breanne; Maze, Dawn
Abstract : BACKGROUND: There is little evidence to guide management of patients with acute leukemia and intracranial hemorrhage (ICH). Predictors of long‐term outcome following ICH are unknown. STUDY DESIGN AND METHODS: This study included adult patients with acute leukemia and ICH over an 8‐year period. The primary outcome was data regarding 90‐day mortality. Secondary outcomes included data related to the proportion of patients receiving post‐remission therapy and predictors of 90‐day mortality. RESULTS: ICH occurred in 101 patients; 12 patients died within 72 hours. For the 89 others, 90‐day mortality was 40%. Of 43 patients who received induction, 30 achieved remission and 26 received post‐remission therapy. Older age (p = 0.03) and higher white count (p = 0.02) at the time of ICH were predictive of inferior survival. During 90‐day follow‐up, median platelet count was 37 x 10 9 /L (0‐1526 x 10 9 /L). Lower platelet count during follow‐up was predictive of 90‐day mortality (p = <0.01). Twenty‐one percent of platelet transfusions were provided when the platelet count was less than 10 x 10 9 /L, 54% between 10 and 29 x 10 9 /L, and 25% greater than 30 x 10 9 /L. New or progressive ICH occurred in 23 patients. There was no difference in the median platelet transfusion trigger between patients who had new or progressive ICH and those who did not. CONCLUSION: In patients with acute leukemia, survival following ICH is poor. Older age and higher white count is associated with increased mortality, perhaps reflecting higher risk disease. Following ICH in acute leukemia platelet transfusions do not appear to alter the risk of progressive bleeding or mortality.